COMPARATIVE LEGAL ANALYSIS OF HEALTH SYSTEMS IN THE RUSSIAN FEDERATION AND SWITZERLAND - S. Gusakova, Yuliya; Andrey Vladislavovich , Krotov; V. Kuzmina, Alevtina; A. Ragozina, Natalia; Y. Shvets, Yuri (Gênero & Direito, 2020)
This article is devoted to a comparative legal analysis of healthcare systems in Russia and in Switzerland. The fundamental differences are identified. The legal nature of the healthcare system, the implementation of state control in the field of healthcare in the Russian Federation and in Switzerland, as well as promising directions for overcoming them are revealed.